Translation as Evidence in a Court of Law - Ratkus, Artūras (Vertimo studijos, 2025)
This article is one of the first studies to examine the use of translation as evidence in Lithuanian court proceedings. It outlines the ways translation enters the judicial process, the involvement of translators and expert linguists, and their respective roles in the process of translation and assessment. Drawing on three case studies, the article demonstrates how translation can itself become challenged in court and analyses the approaches courts employ when assessing the language of the original in relation to the translated text. It draws attention to questionable or flawed practices in determining meaning and raises concerns about the limited linguistic competence of judicial decision makers. It also addresses issues relating to the role and responsibility of the expert linguist.
Keywords: translation; translator; expert linguist; expert report; evidence; court